CONCEPTUALIZATION OF THE CREDIT INSTITUTIONS’ FINANCIAL STABILITY PROVIDING PROCESS - Хуторна , Мирослава (Socio-economic relations in the digital society, 2019)
This paper is dedicated to the process of the credit institutions’ financial stability providing. The author pays attention to the factors of this process, its subjects and objects. The structuring of the selected factors was being done by the use of the Isikava method (so called Fishbone Diagram) that grounds on the factors’ Cause & Effect Analysis. This technique allows to present the factors set as a scale of ranks and reveal principal reasons as well as the resulting motives that directly cause the credit institutions’ financial stability level changes. We reckon that the 1st level factors (the resulting ones) are: the level of demand on the credit institution’s services; an effectiveness of the supervision system; the substantiation of the credit institution’s development strategy; an effectiveness of the credit institution’s business-processes organization and management; the level of the institution’s financial firmness. Further working outs help us to reveal the basic factors (IIIrd level) which include internal and external factors that is analogous to the previous factors’ ranks. This gives us grounds for identifying direct and mediated subjects who influence on the credit institution’s financial stability providing. And also we  substantiate the objects which must be the targets of the institution’s management in order to achieve purpose-oriented level of the financial stability.
Keywords: credit institutions’ financial stability; factors of the credit institutions’ financial stability providing; subjects of the credit institutions’ financial stability providing; objects of the credit institutions’ financial stability providing